1990
DOI: 10.1002/jctb.280490104
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative detoxification of aqueous bark extracts. Part I: Autoxidation

Abstract: The aqueous extracts of bark were studied as a model for wet debarking wastewater. These extracts are known to contain a high concentration of methanogenic toxic tannins. The objective of this study was to modify the native bark tannins (oligomers) with oxidative methods in order to decrease their methanogenic toxicity. The tannins were polymerized by autoxidation, forming colored high-molecular-weight tannins that were non-toxic to methanogenic bacteria. The autoxidation of pine bark extracts provided complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The results obtained in this study confirmed that extended aeration of the anaerobically treated effluent promotes the oxidative transformation of MNA derivatives, particularly under mild alkaline conditions, suggesting the possibility of utilizing such process for effluent treatment. Alkali-catalyzed autoxidation has been shown previously to be an effective method to detoxify tannins, a major class of polyphenolic compounds, by promoting formation of high molecular weight polymers with reduced ability to interact with biological targets due to steric hindrance (Field et al, 1989; Field et al, 1990). Similarly to aromatic amines such as MPD, polyphenolic compounds undergo rapid autoxidation reactions that cause extensive polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained in this study confirmed that extended aeration of the anaerobically treated effluent promotes the oxidative transformation of MNA derivatives, particularly under mild alkaline conditions, suggesting the possibility of utilizing such process for effluent treatment. Alkali-catalyzed autoxidation has been shown previously to be an effective method to detoxify tannins, a major class of polyphenolic compounds, by promoting formation of high molecular weight polymers with reduced ability to interact with biological targets due to steric hindrance (Field et al, 1989; Field et al, 1990). Similarly to aromatic amines such as MPD, polyphenolic compounds undergo rapid autoxidation reactions that cause extensive polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…Due to increasingly strict regulations on effluent discharge both in Sudan and globally [3], it has become necessary to find ways to fully utilize vegetable tannins and reduce the environmental impact of the tanning process. Several methods have been proposed to achieve this goal, such as pickle less vegetable tanning [12], oxidative degradation of tannin liquors using hydrogen peroxide [13][14], precipitation using zinc sulfate [15], and oxidative detoxification of bark extracts [16]. These methods aim to reduce the pollution load in effluents and promote a more sustainable tanning industry.…”
Section: Introductionmentioning
confidence: 99%